The 4-aminopiperidine series has limited anti-tubercular and anti-staphylococcus aureus activity - Chandrasekera, N Susantha (J Negat Results Biomed, 2015)
BACKGROUND: Tuberculosis (TB) caused by Mycobacterium tuberculosis is the leading cause of death from a bacterial infection. The 4-aminopiperidine (PIP) series has been reported as having anti-bacterial activity against M. tuberculosis. We explored this series for its potential to inhibit aerobic growth of M. tuberculosis. We examined substitution at the N-1 position and C-4 position of the piperidine and modifications of the piperidine moiety systematically to delineate structure-activity relationships influencing potency. Compounds were tested for growth-inhibitory activity against virulent M. tuberculosis. A selected set of compounds were also tested for its activity against Staphylococcus aureus. RESULTS: The compound with a norbornenylmethyl substituent at the N-1 position and N-benzyl-N-phenethylamine at the C-4 position of the piperidine (1) was the only active compound with a minimum inhibitory concentration (MIC) of 10 μM against M. tuberculosis. Compounds were not active against S. aureus. CONCLUSIONS: We were unable to derive any other analogs with MIC < 20 μM against M. tuberculosis. Therefore we conclude that the lack of activity is a liability in this series precluding it from further development.